Peran Guru Dalam Dalam Menanamkan Nilai-Nilai Karakter Siswa Kelas VIII Di Sekolah Menengah Pertama Negeri 1 Talibura Kecamatan Talibura Kabupaten Sikka - Yosep Arianto; Moh.Fitri; Rudolfus Ali (Garuda: Jurnal Pendidikan Kewarganegaraan Dan Filsafat, 2023)
The problem of this research is about the role of teachers in instilling Character Values ​​in class VIII students at the Talibura 1 State Junior High School. The aim of this research is to describe the role of teachers in instilling character values ​​in class VIII students at SMP Negeri 1 Talibura and to determine the driving and inhibiting factors. The method used in this research is a descriptive qualitative research approach. Qualitative descriptive research is research that is a type of qualitative research. It is hoped that this research will be able to provide an overview or tell about the role of teachers in instilling character values ​​in class VIII students at SMP Negeri 1 Talibura. The conclusion of this research is that teachers are good, but because there are still some children who violate school rules, teachers must maximize their role and encouraging and inhibiting factors in instilling students' character values. For this reason, cooperation between parents and the school environment is especially important for teachers. because controlling juvenile delinquency is not only done by teachers but by teachers, families and the school environment. For this reason, it is recommended that teachers at SMP Negeri 1 Talibura must try to carry out their role optimally in tackling juvenile delinquency at school. Must always be happy to provide motivation, direction, guidance and habituation. Role models, and supervision and emphasis on students so that they can become human beings who are capable of speech and behavior, in everyday life